2011
DOI: 10.1016/j.hkjot.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Adeli Suit Therapy on Improvement of Gross Motor Function in Children with Cerebral Palsy

Abstract: Objective: This study aimed to investigate the effects of the Modified Adeli suit therapy (MAST) on improvement of gross motor function in children with cerebral palsy (CP). Methods: Thirty-six children with CP assigned by match pairs to three equal groups such as the MAST, the AST, and the Neurodevelopmental Treatment. They were treated for 4 weeks, 2 hr/d,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 22 publications
0
35
0
7
Order By: Relevance
“…Mahani et al 41 studied 36 children with a diagnosis of spastic CP (diplegia and quadriplegia) and dystonic CP (quadriplegia) with severity (GMFCS levels I, II, III, and IV). There were three training groups: the Modified Adeli suit therapy (MAST), the AST, and the NDT groups.…”
Section: 57mentioning
confidence: 99%
See 4 more Smart Citations
“…Mahani et al 41 studied 36 children with a diagnosis of spastic CP (diplegia and quadriplegia) and dystonic CP (quadriplegia) with severity (GMFCS levels I, II, III, and IV). There were three training groups: the Modified Adeli suit therapy (MAST), the AST, and the NDT groups.…”
Section: 57mentioning
confidence: 99%
“…The severity level of children with CP was not specified according to the GMFCS. The results showed a statistically significant difference between groups (p=0.030), which indicated that modified suit therapy was effective in improving the gross motor function in children with spastic diplegia CP (Table I).Mahani et al 41 studied 36 children with a diagnosis of spastic CP (diplegia and quadriplegia) and dystonic CP (quadriplegia) with severity (GMFCS levels I, II, III, and IV). There were three training groups: the Modified Adeli suit therapy (MAST), the AST, and the NDT groups.…”
mentioning
confidence: 99%
See 3 more Smart Citations